Penentuan Nilai Sun Protection Factor (SPF) Ekstrak Air dan Kloroform Daun Kelor (Moringa oleifera L.) - Litta ‘Ifina; Fadilah Qonitah; Risma Sakti Pambudi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Moringa (Moringa oleifera) is a plant that is easy to grow in lowlands that contains phenolic compounds and flavonoids that have the potential to be sunscreen. The purpose of this study is to determine the activity of sunscreen from water extract and chloroform of moringa leaves as seen from the SPF parameters. The process of making extracts by infusion and maceration methods. Testing of SPF values with the UV-Vis spectrophotometer method. The SPF (Sun Protection Factor) value was determined using a UV-Vis spectrophotometer by measuring absorbances from concentrations of 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm water extract solutions and chloroform moringa leaves at wavelengths (290-320 nm) every 5 nm intervals with ethanol pa as a blank. The calculation of the SPF (Sun Protection Factor) value uses the Mansyur equation. The experiments that have been carried out have obtained results that there is sunscreen activity with the highest SPF value in water extract with a concentration of 250 ppm of 7.97 (extra protection) and in chloroform extract with a concentration of 250 ppm of 8.72 (ultra protection). Based on this study, it can be concluded that chloroform extract has a higher SPF value content compared to moringa leaf water extract at the same concentration.